Optimized sampling to estimate vancomycin drug exposure: Comparison of pharmacometric and equation‐based approaches in a simulation‐estimation study - David W. Uster; Sebastian G. Wicha (Wiley, 2022)
Abstract Vancomycin dosing should be accompanied by area under the concentration‐time curve (AUC)-guided dosing using model‐informed precision dosing software according to the latest guidelines. Although a peak plus a trough sample is considered the gold standard to determine the AUC, single‐sample strategies might be more economic. Yet, optimal sampling times for AUC determination of vancomycin have not been systematically evaluated. In the present study, automated one‐ or two‐sample strategies were systematically explored to estimate the AUC with a model averaging and a model selection algorithm. Both were compared with a conventional equation‐based approach in a simulation‐estimation study mimicking a heterogenous patient population (n = 6000). The optimal single‐sample timepoints were identified between 2-6.5 h post dose, with varying bias values between −2.9% and 1.0% and an imprecision of 23.3%-24.0% across the population pharmacokinetic approaches. Adding a second sample between 4.5-6.0 h improved the predictive performance (−1.7% to 0.0% bias, 17.6%-18.6% imprecision), although the difference in the two‐sampling strategies were minor. The equation‐based approach was always positively biased and hence inferior to the population pharmacokinetic approaches. In conclusion, the approaches always preferred samples to be drawn early in the profile (<6.5 h), whereas sampling of trough concentrations resulted in a higher imprecision. Furthermore, optimal sampling during the early treatment phase could already give sufficient time to individualize the second dose, which is likely unfeasible using trough sampling.